MOTIVASI PETANI MEMBUDIDAYAKAN TANAMAN OBAT DI KECAMATAN ,JUMAPOLO KABUPATEN K.ARANGANYAR - Widiyanto Widiyanto (Universitas Sebelas Maret, 2005)
Jumapolo Subdistrict is area of Development Superior Commodities Agricultural Center of herbal medicine specially